Prevalence of metabolic syndrome and associated factors among psychiatric patients at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia. - Nigist Alemayehu Woldekidan; Ammas Siraj Mohammed; Amsalu Degu; Yohannes Tadiwos (PLoS ONE, 2021)
Background Psychiatric patients are at increased risk of being overweight or obese, and subsequently develop metabolic syndrome. Nevertheless, data regarding associated factors for weight gain are limited and inconsistent. Objective The present study aimed to determine the risk of metabolic syndrome and its associated factors among psychiatric patients. Method A cross-sectional quantitative study was conducted among all psychiatric patients at the Psychiatric Unit of the University of Gondar Comprehensive Specialized Hospital from March 1- April 1, 2018. All eligible psychiatric patients were interviewed about their socio-demographic status,and clinical characteristics and useful parameters for the study were recorded from the medical records of the patients and by measuring waist to height ratio. Descriptive statistics were used to summarize baseline information.Binary logistic regression was used to determine the associated factors and P-value <0.05 and confidence interval (CI) of 95% were used as cut off points for determining statistical significance. Result From 300 patients included in the study, 168(56%) patients were females,and around 50.3% of the study participants had low literacy levels. As per waist to a height ratio scale, 58% (174) of the patients had a risk of metabolic syndrome. The Binary logistic regression analysis indicated that sex (p-<0.0001), occupation (p -0.032), marital status (p-0.006), and distance from the hospital (p<0.0001) were statistically significant determinants of metabolic syndrome risk in the psychiatric patient in our setting. Conclusion The majority of the psychiatric patients in the study setting had a risk of metabolic syndrome. Sex, marital status, employment status, and distance to the hospital were significantly associated with metabolic syndrome. Routine physical and laboratory investigations to detect metabolic syndrome are indispensable in psychiatric patients to prevent cardiovascular complications.